Observations on the role of frugivorous bats as seed dispersers in Costa Rican secondary humid forests - Lopez, Jorge E. (2004)
The role of frugivorous bats as seed dispersers in humid neotropical tropical forests was evaluated between January and August 1995. Thirty germination trials were set up using seeds defecated by six bat species. Seeds of Piper multiplinervium and Ficus insipida, defecated by Carollia brevicauda and Artibeus jamaicensis, respectively, showed significantly higher germination percentages than seeds not ingested by bats. Of seven seed species regurgitated by bats, only Markea neurantha showed significant increases in percent germination compared to seeds not ingested by bats. Of 19 tents and three active feeding roosts found, 12 tents and three feeding roosts were in primary forest, while six tents were in abandoned plantations. For tent construction, four bat species used six plant species. Fifty-two percent of seeds found under tents and feeding roosts were from secondary forest species. Twenty-two percent of seed species in fecal samples from netted bats in three secondary forest types were primary forest species. Bats in our study dispersed seeds between different habitat types.